Intervening in Academic Procrastination through MCII: A Theory-Based Model for Smart Learning Environments to Support Sustainable Development Goals - Xiaoxue, Zhou; Walton, Wider; Yukun, Liao (INTI International University, 2025)
Academic procrastination poses a significant challenge in higher education, particularly within digitally mediated and autonomous learning environments. This issue not only affects individual academic performance but also undermines broader efforts to achieve Sustainable Development Goal (SDG) 4, which aims to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. This conceptual paper introduces an integrated framework combining the Temporal Decision Model (TDM) with Mental Contrasting and Implementation Intentions (MCII) to address procrastination as a barrier to educational sustainability. The proposed model leverages AI-supported smart education systems to deliver scalable, cost-effective interventions, aligning with SDG 9 (Industry, Innovation, and Infrastructure) and SDG 17 (Partnerships for the Goals). By fostering self-regulation and resilience, this framework contributes to creating adaptive, future-ready learners capable of navigating global challenges.